2004
DOI: 10.1002/pssb.200304163
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the optical and magnetic properties of II–VI quantum dots by post‐growth rapid thermal annealing

Abstract: We show that both the optical and magnetic properties of CdTe-based quantum dots (QDs) can be tuned by post-growth annealing. With increasing of annealing temperature, the photoluminescence of CdTe and CdMnTe QDs shifts towards high energies. At the same time, we observe a narrowing of the QD ensemble emission linewidth due to the improved homogeneity of the QD ensemble. We find that for annealed CdTe QDs the exciton diamagnetic shift is about two times larger that for the as-grown ones, suggesting an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…One can see that the polarization of EMPs increases rapidly at higher excitation energies. This observation suggests that the optically induced magnetization of the EMPs in CdMnTe depends on the QD energy [54]. It shows that the photo-induced magnetization is stronger for QDs with lower Mn concentration.…”
Section: Resultsmentioning
confidence: 85%
“…One can see that the polarization of EMPs increases rapidly at higher excitation energies. This observation suggests that the optically induced magnetization of the EMPs in CdMnTe depends on the QD energy [54]. It shows that the photo-induced magnetization is stronger for QDs with lower Mn concentration.…”
Section: Resultsmentioning
confidence: 85%
“…As we reported previously, diffusion is strongly enhanced below the SiO 2 mask as compared to non-covered areas 42 and results in the increase of bandgap below the masked areas, inducing a lateral confine- ment potential up to 0.3 eV 42 depending on the sample and processing parameters. It was shown that RTA technique allows to vary the QW energy gap in a controllable way with a good optical quality 40,41,42 . QW, located between two CdMgTe barriers, incorporates only Mg atoms after RTA and is referred to as nonmagnetic well (NMW) whereas that with CdMnTe barrier contains both Mg and Mn atoms and is referred to as magnetic well (MW).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the RTP technique has been used for tailoring the optical and magnetic properties of Mn-doped CdTe-based quantum dots (QDs) [69,70] and InAs/GaAs self-assembled QD structures (SAQDs) [71]. The preliminary studies showed that RTP led to an increase in the average dot size accompanied by narrowed emission linewidth of the individual magnetic dot.…”
Section: Spintronic Materialsmentioning
confidence: 99%